Intelligent coordinator selection mechanism (ICSM) for IEEE802.15.4 beacon-enabled MAC protocol in mobile wireless sensor networks - Zen, K.; Javed, M.; Lenando, H.; Zen, H.; Khan, A.S. (Praise Worthy Prize, 2015)
The IEEE802.15.4 beacon-enabled MAC protocol supports a simple coordinator selection mechanism (CSM) in static WSNs as well as mobile WSNs, where CSM normally selects the nearest coordinator. However, CSM is not suitable for constant moving node in mobile WSNs, where node will be switching coordinators too often due to strong mobility and low coverage range. In mobile WSNs, the node needs to select the best coordinator that has potential to provide longest connectivity period. This paper introduces the Intelligent Coordinator Selection Mechanism (ICSM) which supports the node to select the best coordinators. The proposed mechanism is based on link quality indicator (LQI) values of the received beacon frames from the nearby coordinators. The node selects the coordinator for association that has potential to provide the longest connectivity period. Our proposed ICSM reduces the energy consumption, enhance the association period and the throughput, and minimize the number of switching amongst the coordinators. The mobile node connectivity period is improved from 55% to 86% (static) and 94% (mobile), while the number of association attempts are reduced from 13% to 6% (static) and 2% (mobile) coordinators.